Enhanced degradation of quinoline in three-dimensional electro-Fenton system through NiCo2S4/g-C3N4 particles - Jun Chen; Boding Zhang; Bingxing Wang; Chengxing Cui; Songlin Wang; Jichao Wang; Wenlong Zhang (Arabian Journal of Chemistry, 2023)
The stability and toxicity of quinolines are difficult to degrade by conventional physicochemical and biological methods, posing a threat to human health and the environment. In this study, we prepared NiCo2S4/g-C3N4 particles and applied them in an electrochemical reactor to form a three-dimensional catalytic particle electro-Fenton system (3D-EF), which can efficiently remove quinoline from wastewater. The NiCo2S4/g-C3N4 catalytic particles were characterized by XRD, SEM, TEM, XPS. The optimum conditions for 3D-EF were 30 min reaction time, 60 g/L NiCo2S4/g-C3N4 particles dosage, pH value of 3, 67.6 mmol/L H2O2 concentration, 12.1 ms/cm conductivity and 5 A current. Under the optimum conditions, a chemical oxygen demand (COD) removal rate of 95.6% was achieved. NiCo2S4/g-C3N4 catalytic particles can be easily recovered by filtration and can be reused. Kinetic analysis showed that the COD degradation of quinoline solutions by the 3D-EF followed a first-order kinetic model. To determine the important role of hydroxyl radicals in the electrochemical process, electron paramagnetic reaction (EPR) and radical scavenging experiments were performed. Finally, in order to elucidate the degradation mechanism, the intermediates were identified by high performance liquid chromatography-mass spectrometry (HPLC-MS) and two possible degradation pathways were proposed. Meanwhile, the biochemical analysis of quinoline wastewater was also performed.